2022
DOI: 10.1007/s12671-022-01912-9
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Mindfulness Skills and Positive and Negative Affect and Their Interrelationships During Mindfulness-Based Cognitive Therapy for Cancer Patients

Abstract: Objectives While efficacy research on mindfulness-based interventions in cancer patients is available, research on possible mechanisms of change is lacking. The current study investigated general and week-to-week changes and interrelations in mindfulness and positive and negative affect in Mindfulness-Based Cognitive Therapy (MBCT) for cancer patients. Methods In total, 163 cancer patients completed face-to-face or online MBCT. Mindfulness and positive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…The second finding of the research showed that MBCT was effective in reducing rumination in students with psychological distress. This finding is consistent with the results previous studies (Cillessen et al, 2022;Foroozandeh & entezari, 2020;Frostadottir & Dorjee, 2019;Grensman et al, 2018;Hervás et al, 2016;Kocsis & Newbury-Helps, 2016;Tavakoli & Ebrahimi, 2020). Regarding the effectiveness of MBCT, the primary focus is on present moment mental events in a non-judgmental state, helping individuals to recognize and perceive their negative emotions without avoidance or punishment and without drowning in those emotions, but instead considering mental events as transient and passing (Foroozandeh & entezari, 2020;Frostadottir & Dorjee, 2019;Grensman et al, 2018;Kocsis & Newbury-Helps, 2016).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The second finding of the research showed that MBCT was effective in reducing rumination in students with psychological distress. This finding is consistent with the results previous studies (Cillessen et al, 2022;Foroozandeh & entezari, 2020;Frostadottir & Dorjee, 2019;Grensman et al, 2018;Hervás et al, 2016;Kocsis & Newbury-Helps, 2016;Tavakoli & Ebrahimi, 2020). Regarding the effectiveness of MBCT, the primary focus is on present moment mental events in a non-judgmental state, helping individuals to recognize and perceive their negative emotions without avoidance or punishment and without drowning in those emotions, but instead considering mental events as transient and passing (Foroozandeh & entezari, 2020;Frostadottir & Dorjee, 2019;Grensman et al, 2018;Kocsis & Newbury-Helps, 2016).…”
Section: Discussionsupporting
confidence: 94%
“…The primary mechanism of mindfulness is attention regulation because focusing attention repeatedly on a neutral stimulus like breathing creates a suitable attentional environment (Foroozandeh & entezari, 2020;Hertenstein et al, 2012;Tavakoli & Ebrahimi, 2020). Mindfulness-based training, by correcting negative cognitions, allows for dialogue and engagement with life's problems and decisionmaking, reducing negative emotions, pressure, stress, anxiety, and consequently, feelings of energy depletion, fatigue, and sadness, meaning a reduction in depression (Cillessen et al, 2022;Tavakoli & Ebrahimi, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mindfulness – a psychological state where an individual is consciously aware of his or her present moment – has been shown to decrease negative affect (e.g. Lancaster et al ., 2016; Crosswell et al ., 2017; Cillessen et al ., 2022). Therefore, organizations can organize mindfulness meditation at work to weaken the linkage between abusive supervision, negative affect and cyberloafing.…”
Section: Discussionmentioning
confidence: 99%